DISPUTE RESOLUTION METHODS THROUGH THE CONSUMER DISPUTE RESOLUTION AGENCY - Andini Prameswari (UM.Tapanuli Selatan, 2024)
Consumer law is included in civil law in a broad sense, namely Civil Law and Commercial Law. In Indonesia, consumer protection issues began in the 1970s, marked by the establishment of the Indonesian Consumers Foundation in May 1973. This study uses a normative legal research method, the results of the study show that the Indonesian government created Law Number 8 of 1999 concerning Consumer Protection, to accommodate the interests and protection of consumers and business actors. The Consumer Dispute Resolution Agency has several dispute resolution methods using the Mediation, Conciliation, and Arbitration methods.